Hubungan Pengetahuan Kesehatan Reproduksi Siswa terhadap Sikap Pencegahan Penyakit Menular Seksual Di Kelas XI SMA Negeri 2 Samarinda - Diah Pratiwi; Zenia Lutfi Kurniawati; Vandalita Maria Magdalena Rambitan; Suparno Putera Makkadafi (UNIB Press, 2026)
This study aims to analyze the relationship between reproductive health knowledge and attitudes toward the prevention of sexually transmitted diseases among students. This study employs a quantitative approach using a correlational method. Data collection was conducted by distributing questionnaires to students as research respondents. The obtained data were analyzed using normality tests and correlation product moment tests. The results indicate that the data are normally distributed. Based on the results of correlation product moment test, a correlation coefficient of 0.449 was obtained, which falls into the moderate category, indicating a positive relationship of moderate strength between reproductive health knowledge and attitudes toward the prevention of sexually transmitted diseases among students. This positive relationship suggests that the higher the level of reproductive health knowledge students possess, the better their attitudes toward preventing sexually transmitted diseases. The moderate strength of the association indicates that knowledge of reproductive health is not the only factor influencing attitudes toward the prevention of sexually transmitted infections.